BeetRepeats: reference sequences for genome and polymorphism annotation in sugar beet and wild relatives - Nicola Schmidt; Sophie Maiwald; Ludwig Mann; Beatrice Weber; Kathrin M. Seibt; Sarah Breitenbach; Susan Liedtke; Gerhard Menzel; Bernd Weisshaar; Daniela Holtgräwe; Tony Heitkam (BMC Research Notes)
Abstract Objectives Despite the advances in genomics, repetitive DNAs (repeats) are still difficult to sequence, assemble, and identify. This is due to their high abundance and diversity, with many repeat families being unique to the organisms in which they were described. In sugar beet, repeats make up a significant portion of the genome (at least 53%), with many repeats being restricted to the beet genera, Beta and Patellifolia. Over the course of over 30 years and many repeat-based studies, over a thousand reference repeat sequences for beet genomes have been identified and many experimentally characterized (e.g. physically located on the chromosomes). Here, we present the collection of these reference repeat sequences for beets. Data description The BeetRepeats_v1.0 resource is a comprehensive compilation of all characterized repeat families, including satellite DNAs, ribosomal DNAs, transposable elements and endogenous viruses. The genomes covered are those of sugar beet and closely related wild beets (genera Beta and Patellifolia) as well as Chenopodium quinoa and Spinacia oleracea (all belonging to the Amaranthaceae). The reference sequences are in fasta format and comprise well-characterized repeats from both repeat categories (dispersed/mobile as well as tandemly arranged). The database is suitable for the RepeatMasker and RepeatExplorer2 pipelines and can be used directly for any repeat annotation and repeat polymorphism detection purposes.